Superiors’ Participatory Management Behaviour: Perception of Agriculture Officers in Banking Sector (Indian Journal of Extension Education, 2023)
The quality of the superior-subordinate relationship can significantly impact various aspects of participatory management behaviour. The study was conducted in 2022 to assess the superiors’ behaviour as perceived by a randomly selected 180 agriculture officers working in public sector banks in the state of West Bengal. Superiors’ behaviour was assessed based on the four domains; motivation, communication, coordination, and empathy which included 20 aspects on which responses of the selected agriculture officers were obtained on a 5-point continuum scale. Superiors’ behavioural characteristics were derived by mean perception score. Superiors’ motivating nature was found to be most admired by the respondents. Using ANOVA and post hoc tests, significant differences were identified between the groups of agriculture officers categorised based on the job experience in the banks with respect to various dimensions of superiors’ behaviour. Respondents with experience of >10 years perceived overall superiors’ behaviour lowly (68.49) as compared to the other two groups with experience of up to five years (75.86) and >5-10 years (75.27), respectively. Such differences based on experience need to be addressed to create a more cohesive and thriving work environment for the agriculture officers in the banking sector to provide better financial assistance to the farmers.